1997
DOI: 10.1155/1997/821241
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of carboline

Abstract: The reactions of carboline under various oxidative conditions are reported. The soft aerobic radiolysis, hydroxylation and rearrangement transformations are studied using isotopic labelling and GC–MS techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Under strict temperature and time control as applied in the here-described experiments, an intramolecular shift of the oxygen is very unlikely. Furthermore, the proposed structure of 3 was also supported by the radiolysis of 2-thiopyridine derivatives (23). Sulfoxides instead of N-oxides were observed as reaction products.…”
Section: Isolation and Structure Elucidation Of The Precursormentioning
confidence: 71%
See 1 more Smart Citation
“…Under strict temperature and time control as applied in the here-described experiments, an intramolecular shift of the oxygen is very unlikely. Furthermore, the proposed structure of 3 was also supported by the radiolysis of 2-thiopyridine derivatives (23). Sulfoxides instead of N-oxides were observed as reaction products.…”
Section: Isolation and Structure Elucidation Of The Precursormentioning
confidence: 71%
“…1 H NMR (500. 16 MHz, acetonitrile-d 3 ): δ 1.14 (s, 9, H22, H22, H22, H23, H23, H23, H24, H24, H24), 3.56 (dd, 1, J = 14.03, 10.02 Hz, H8), 3.89 (dd, 1, J = 14.03, 4.58 Hz, H8), 5.84 (dd, 1, J = 10.02, 4.58 Hz, H9), 6.88 (dt, 1, J = 0.86, 8.31 Hz, H15), 6 (10), 61 (23), 63 (26), 78 (9), 93 (100), 109 (11), 111 (11), 112 (12), 126 (4), 142 (3) 174 (5), 220 (5). Sodium adduct C 7 H 9 NOS 3 Na: HR-ESI-MS, 241.9749; MS calculated, 241.9744.…”
Section: Hplc Separation Of Thementioning
confidence: 99%
“…Hence in search for new HAT chemotherapy Dardonville C et al [57] decided to carry out an in vitro screening of a total of 62 compounds against the parasite T. brucei rhodesiense taken from their in-house library. Based on this they showed that bisguanidine and especially bis(2-aminoimidazoline)diphenyl compounds displayed potent anti-trypanosomal activity in vitro and vivo against T. b. rhodesiense, the causative agent of acute HAT [58,59]. Among the 62 compounds screened, compounds1c, 28b, 32b and 41b ( Figure 17) showed excellent in vitro activity (49nM, 69 nM, 22 nM and 118 nM respectively) as well as high selectivity (>5294, 3072, 29.5 and 881respectively) for the parasite.…”
Section: Bis(2-aminoimidazoline) and Bisguanidinementioning
confidence: 99%